Pengaruh Penerapan Model Pembelajaran Kooperatif Tipe Numbered-Head Together (Nht) Terhadap Peningkatan Aktivitas Belajar Siswa - Arini Alhaq; Uus Manzilatusifa; Bella Anantha Sritumini (Program Studi Pendidikan Ekonomi, FKIP Universitas Langlangbuana, 2015)
The learning model Numbered-Head Together (NHT) is one model that can be influenced to improve students' learning activities meaningful learning model Numbered-Head Together (NHT) focus more on the students to groups that are designed to affect the pattern of interaction of students and provide opportunities for students to participate actively in the learning process so as to achieve the learning objectives in accordance with the learned. With the formulation of the problem that arises that is: how much influence is the application of the Numbered-Head Together (NHT) Co-operative Learning Model to the improvement of student learning activities?